Предмет:
МатематикаАвтор:
анонимЗапишем сумму и разности двух выражений и упростим их:
a) -4 - 7 * a и -a + 3,2 * a + 2,5 * a;
-4 - 7 * a + (-a + 3.2 * a + 2.5 * a) = -4 - 7 * a - a + 3.2 * a + 2.5 * a = -4 - 8 * a + 5.7 * a = -4 - 8 * a + 5 * a + 0.7 * a = -4 - 3 * a + 0.7 * a = -4 - 2.3 * a;
-4 - 7 * a - (-a + 3.2 * a + 2.5 * a) = -4 - 7 * a + a - 3.2 * a - 2.5 * a = -7 - 6 * a - 5.7 * a = -7 - 11.7 * a;
b) 3,1 * n - 5 и 9 * n - 10,5 * n + 6;
3.1 * n - 5 + 9 * n - 10.5 * n + 6 = 1 + 3.1 * n - 1.5 * n = 1 + 1.6 * n;
3.1 * n - 5 - 9 * n + 10.5 * n - 6 = 1.5 * n - 11 + 3.1 * n = -11 + 4.6 * n;
b) -b + 6,3 и 15 * b - 17,2 * b - 8 * b;
-b + 6.3 + 15 * b - 17.2 * b - 8 * b = 6.3 - 11.2 * b;
-b + 6.3 - 15 * b + 17.2 * b + 8 * b = 6.3 + 9.2 * b.
Автор:
isabellajohnsonДобавить свой ответ
Предмет:
МатематикаАвтор:
анонимОтветов:
Смотреть
Предмет:
МатематикаАвтор:
анонимОтветов:
Смотреть
Предмет:
МатематикаАвтор:
анонимОтветов:
Смотреть
Предмет:
МатематикаАвтор:
анонимОтветов:
Смотреть